As determinações da moralidade na obra de Marx - Ana Selva Castelo Branco Albinati (2007)
This work intends to present the considerations of Karl Marx about the morality, with the objective to organize, in the limits of our possibilities, an aspect from the authors work that appears scattered through of it.Being a continuation of the research made during our master, that deals with Marxs texts from 1841 to 1847, the objective now is to check the permanences, the ruptures and the new considerations offered by the author about these question, articulating the previous study and revising the obtained results by examination of his maturitys writings, especially The Capital-I, the Grundrisse and Theories of Surplus Value, to demonstrate the reconfiguration realized by Marx between the spheres of social life, in confrontation with authors that work in both areas: economic science and moral philosophy, especially Adam Smith and John Stuart Mill.The thesis to be demonstrated is that Marx understands the proposition of these economists about the relation economy-morality as a phenomenical comprehension of the real concrete relations. As a consequence of these reconfiguration, an original field is opened to review main questions of ethical reflection, such as individual-society relation, the determination of the will, the freedom, the nature and weight of the moralitys rules in the social life.